The allergic potential arising from proteinous wine fining agents of milk and chicken egg albumen - Webber-Witt, Manuella; Justus Liebig University Giessen (My University, 2014)
This study investigated whether technological procedures could be used to avoid allergic residues remaining in wine, after the use of fining agents containing milk or egg protein. Fining materials used during the wine making process when derived from milk or egg may present the possibility to trigger an allergic reaction. Therefore these substances should be declared on the wine label if present in the final product, depending on the legislation of each country. Label information enables allergic consumers to avoid food and beverages that may trigger allergic symptoms. As there is no standard for the sequence of winemaking practices a fining trial was conducted to study the influence of various filtration and further methods normally used in the wine industry and its efficiency on reducing this possible allergens, even in a worst case scenario. More than nine different German wines, red and whites from different years were used on this study. The methods used to detect the residues were different ELISA assays and in vivo tests were evaluated with allergic patients, prick skin test and Double-blind, placebo-controlled food challenge (DBPCFC) with fined wines, where none of the patients tested reacted allergically. Casein is removed from both red and white wines to not detectable levels by all methods of filtration used in this work. Centrifugation alone might let some residues behind as well as flash-pasteurisation. Nevertheless an additional sterile filtration after flash-pasteurisation or centrifugation decreases casein proteins to no longer being detectable. For whey protein only a bentonite treatment with successive sterile filtration was found to be competent to reliably reduce the amount of detectable protein below the detection limit of the assay at both concentration levels in both red and white wine used in this study. Albumin residues are present when wine is fined but not filtered, especially white wines, most filtration methods used in this work are capable to bring the residues to no longer being detectable when a normal dosage of fining agent is applied. Flash-Pasteurisation is not advised for wines that have been previously fined with egg white, since there is an increase on the residues after heating practice, when ELISA assay is applied as detection method. Lysozymes stay present in the wine in most cases of this study, in reds and in whites. If a bentonite treatment takes place after the fining, in the legal limits of up to 500 ppm, followed by sterile filtration with 0.45µm pad filter, no residues are detected.Lysozyme reacts with metatartaric acid and with carboxymethyl-cellulose and precipitates, but not completely. Reaction with red wine phenols lead to precipitation, the higher the total phenol content the greater was the enzyme precipitation, here again the precipitation itself was not enough to diminish the lysozyme amount under 0.25 ppm.In conclusion, if wines are fined with low amount of fining agents and properly filtered, they are likely to have no detectable residues. However if a wine is not filtered and casein, whey protein and egg albumin or lysozyme has been applied it should be declared on the label.
Allergene Rückstände im Wein von proteinhaltigen Schönungsmitteln
Keywords: Wein; Schönungsmittel; Casein; Hühnereiweiß; Allergene; wine; fining agents; casein; egg-white; allergy; ddc:630